2016
DOI: 10.3390/ijms17020220
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Omega-3 and Omega-6 Fatty Acids on Allergy Using a HEK-Blue Cell Line

Abstract: Background: Allergic reactions can result in life-threatening situations resulting in high economic costs and morbidity. Therefore, more effective reagents are needed for allergy treatment. A causal relationship has been suggested to exist between the intake of omega-3/6 fatty acids, such as docosahexanoic acid (DHA), eicosapentanoic acid (EPA), docosapentanoic acid (DPA) and arachidonic acid (AA), and atopic individuals suffering from allergies. In allergic cascades, the hallmark cytokine IL-4 bind to IL-4 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In order to increase these applications and also to improve some properties, it is common in polymer industry to under go by synthesis modification [4]. In a recent studies fatty acids demonstrated biological activity [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and some physical properties [19][20][21][22][23][24][25][26][27][28] and its polymers [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase these applications and also to improve some properties, it is common in polymer industry to under go by synthesis modification [4]. In a recent studies fatty acids demonstrated biological activity [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and some physical properties [19][20][21][22][23][24][25][26][27][28] and its polymers [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%